Leadership Dynamics and Institutional Management in Digital Innovation: Reflections on Ciamis Regency Public Services - Fitri Melawati; Rikha Murliasari; Loso Judijanto; Arif Saefudin; Akhlaqur Rahman (Goodwood Publishing, 2026)
Purpose: This study aimed to analyze the role of leadership and institutional design in supporting the successful implementation of digital public services in Ciamis Regency, West Java, Indonesia. Research Methodology: A qualitative research approach was adopted. The study was conducted in Ciamis Regency, involving the Communication and Informatics Office, Population and Civil Registration Office, and sub-district office. Data were collected through in-depth interviews, direct observation for one month, and document analyses. NVivo 12 Plus software was used to analyze and categorize the qualitative data. Triangulation techniques were used to ensure data validity and reliability. Results: The findings show that effective leadership plays a key role in digital transformation through vision-setting, change management, security assurance, performance evaluation, and collaboration building. Institutional design also supports digitalization through strategic planning, adaptive organizational structures, regulatory frameworks and the establishment of digital service teams. Conclusions: Successful digital public service implementation requires a strong synergy between visionary leadership and adaptive institutional management. Technology alone is insufficient without organizational readiness and strategic direction. Limitations: This study is limited to one regional context and relies mainly on qualitative data. Contributions: This study contributes to digital governance, public administration, and policy development by offering practical insights for policymakers and government institutions to improve sustainable digital public services.